A Comparative Evaluation of the Effect of Different Endodontic Irrigating Solutions on Microhardness of Root Canal Dentin: An in vitro Study - Chris Geogi; Sandeep Dubey; Palak Singh; B Rajkumar; Praveen Samant; Ananya Rawat (Shiraz University of Medical Sciences, 2024)
Statement of the Problem: During endodontic therapy, irrigation solutions applied in the root canal may affect the physicochemical properties of the dentinal wall, thereby changing its microhardness. This may adversely affect the sealing ability and adhesion of dental materials. Therefore, many studies have focused on the search for an ideal root canal irrigant that has a minimal effect on dentinal microhardness.Purpose: This in vitro study was conducted to determine the changes in dentin microhardness after root canal irrigation with different endodontic irrigants.Materials and Method: Ninety-five freshly extracted maxillary central incisor teeth with straight single canals were selected. These teeth were sectioned transversely at the level of the cementoenamel junction. The working length of each tooth was determined, and canal space was prepared by the HyFlex CM rotary file system. During instrumentation, normal saline was used for irrigation. Then, teeth were split longitudinally into two segments. According to the irrigating solution employed, samples were divided into five groups (n=19): normal saline (Group A), 3% sodium hypochlorite (Group B), 2% chlorhexidine (Group C), 5% calcium hypochlorite (Group D), and 0.2% nanochitosan (Group E).3 mL of the corresponding irrigating solution was administered for total15 minutes in each prepared sample. The Vickers micro-hardness tester was then used to assess micro-hardness. The data was analyzed using one-way analysis of variance (ANOVA).Results: All tested irrigating solutions decreased the dentinal microhardness. Samples irrigated with 5% calcium hypochlorite demonstrated dentinal microhardness of 42.43± 1.62, which is the lowest among all the tested groups, followed by nano chitosan, sodium hypochlorite, and chlorhexidine. Samples treated with control group (saline) demonstrated the maximum microhardness of dentin in the present study.Conclusion: Within the limitations of this research, it can be concluded that the tested novel irrigating solutions, 5% calcium hypochlorite and 0.2% nanochitosan, were more detrimental to radicular dentin microhardness when compared with conventional endodontic irrigants.